2020
DOI: 10.3329/ajmbr.v6i1.46472
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of discriminate and indiscriminate use of doxycycline in broiler: an indoor research on antibiotic doxycycline residue study in edible poultry tissue

Abstract: Abuse of antibiotics is more common in developing countries including Bangladesh. The aim of this study was to detect doxycycline residue after discriminate and indiscriminate administration in broiler poultry. Eighteen broiler chicks, DOC (Cobb-500) was collected & reared up to 31 days. On day 16, they were randomly divided into 3 groups, namely group–A (Control group), group-B (Discriminate group) and group-C (Indiscriminate group). Each group contains 6 birds. The discriminate and indiscriminate groups … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 10 publications
3
9
0
Order By: Relevance
“…Furthermore, it will be consumer and environment friendly. The results are in accordance with other researchers [12,13,19]. Now a day, alternatives to antibiotic growth promoters is an interesting topic.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Furthermore, it will be consumer and environment friendly. The results are in accordance with other researchers [12,13,19]. Now a day, alternatives to antibiotic growth promoters is an interesting topic.…”
Section: Discussionsupporting
confidence: 92%
“…So, even in discriminate groups, the presence of antibiotics residue was found in liver and kidney. There are other evidences of similar results where kidney and liver was considered the predilection site of antibiotics residues and analyzed accordingly [13,16]. Another study found 60% ciprofloxacin positive samples in broiler meat [22].…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…On day 16, almost similar body weights were observed in all groups (Table-1). On day 31st, the highest body weight was observed in group-C (indiscriminate antibiotic group) and lowest in group-A (Control group) [11,12,13,14]. Differences among the two-antibiotic treated group and control group were observed.…”
Section: Discussionmentioning
confidence: 94%
“…Recently, a good number of studies have been carried out to investigate the presence of the different veterinary drugs including antibiotic residues in animal products [11,12,13,14,15]. The main objective of this study was to screen for the presence of antibiotic residues in poultry meat as well as to know about the growth performance and changes in the hematological parameters.…”
Section: Discussionmentioning
confidence: 99%